ASSESSMENT OF LEARNING MEDIATED BY DIGITAL TECHNOLOGIES: PEDAGOGICAL FOUNDATIONS, HUMANIZED MEDIATIONS, AND ACADEMIC REGULATION - Pereira Nicácio, Jailton; Nogueira de Oliveira , Israel; Estanislau de Oliveira Neto, Antonio; Lisboa Galvão do Nascimento, Jonatha; Modesto Favacho, Kelsin; Helena de Paula Modesto Favacho, Lucia; Santos do Nascimento, Marielza; Campos Rodrigues, Mayara; Ricardo Pereira Accioly, Sérgio (Revista Gênero e Interdisciplinaridade, 2026)
This study aims to investigate the implications of using digital technologies in the assessment of learning, focusing on pedagogical foundations, humanized mediation practices, and the academic standards that guide this process. The research is based on the premise that assessment, as an educational practice, should not only be understood as a tool for measuring outcomes, but as a continuous, reflective, and formative process that fosters the holistic development of the student. In the context of the growing digitalization of education, this work discusses how technologies can be integrated in a critical and humanizing manner, in order to promote a more inclusive and personalized learning experience. Furthermore, it addresses the need for academic standardization to ensure the legitimacy and quality of assessment practices mediated by digital technologies, ensuring that these practices align with pedagogical objectives and ethical principles of education. Therefore, the study seeks to provide a comprehensive analysis of the new assessment configurations in the digital landscape, highlighting the challenges and opportunities for the development of a more democratic and effective education.